Nursing career ladder system in Indonesia: The hospital context - Joko Gunawan; I Gede Juanamasta (Belitung Raya Foundation, 2022)
It is no doubt that being a nurse is very promising in the future, considering the existence and importance of nurses during the COVID-19 pandemic. Therefore, the government is asked to invest more seriously in the advancement of nurses, both in terms of competence and their professional career path. This article focuses on an overview of the nursing career ladder system and how far it is applied in the context of hospitals in Indonesia. Barriers and challenges are also presented for future recommendations.